Genre: a contemporary fallacy? - Beraldo, João Paulo Ribeiro (Em Perspectiva, 2020)
In this article, - the result of my Master's Dissertation -, I intend to work on the idea of gender with a view to its use in history. To this end, I will use as an argumentative basis the American historian Joan Scott, as well as other authors who may be complementary to my expository point. Historically, the idea of “gender” was developed with the intention of “aggregating”, “joining” the two sexes (male and female) in a single discussion space, going beyond debates that unique and exclusively surround women. The main objective of this paper is to demonstrate how such an idea has been used outside its "original intention" and can radiate other conceptions. Some questions need to be answered: Does "gender" (used as a contemporary concept) responds to current social demands? Or is it necessary to revise the use of such a word?